Developing a reverse logistics competency: The influence of collaboration and information technology. Issue 3 (4th April 2016) - Morgan, Tyler R.; Richey Jr, Robert Glenn; Autry, Chad W.
Abstract : Purpose: – The purpose of this paper is to explore the influence of collaboration and information technology (IT) on the reverse logistics competency of firms. Through collaboration firms can improve their ability to handle returns, but this research introduces IT as providing a moderating influence over the impact of collaboration in the advancement of a reverse logistics competency. Design/methodology/approach: – A survey was administered to employees involved with supply chain relationships. Empirical evidence from 267 respondents is analyzed with structural equation modeling. Findings: – Support is found for the positive moderating influence of an IT competency on the relationship between collaboration and a reverse logistics competency. Additional benefits for logistics performance are also realized. Research limitations/implications: – This research provides theoretical implications for the development of a reverse logistics competency through an application of resource-based theory/resource-based view of the firm. The study is limited to the selected research questions and sample of predominantly US firms. Practical implications: – This research assists managers as they attempt to develop a reverse logistics competency to address the growing problem of returns through collaboration with supply chain members and the development of an IT competency. Originality/value: – The framework developed in this research provides insights regarding the handling of product returns. Specifically, the moderating influence of an IT competency is addressed as it enhances the impact of collaboration on the development of a reverse logistics competency.